2006
DOI: 10.1007/s11373-006-9093-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Induced Early Thrombolysis Contributes to Heme Oxygenase-1-Mediated Inhibition of Neointimal Growth after Vascular Injury in Hypercholesterolemic Mice

Abstract: Arterial thrombosis is a critical event in the pathogenesis of lesion development. In this study, we evaluated the effect of heme oxygenase-1 (HO-1), a stress-inducible enzyme with vasoprotective functions, on arterial thrombosis following vascular mechanical injury. The carotid arteries of apoE-deficient mice were subjected to angioplasty with a modified beaded-needle. Arterial thrombosis occurred at 12 h after injury. Treatment of the injured vessels with an adenovirus bearing HO-1 gene (Adv-HO-1) (1Â 10 8 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
5
17
0
Order By: Relevance
“…In other in vitro and in vivo investigations involving either mice or rats [24][25][26][27], COHb concentrations varied following CORM exposure, with little increase seen with CORMs that release CO quickly (e.g., CORM-3, tricarbonyldichloro(glycinato)ruthenium (II)), contrasted with COHb values between 8% to 17% after exposure to slow releasing CORMs (e.g., CORM-A1, sodium boranocarbonate, Na 2 [H 3 BCO 2 ]). In sum, when exposed to CO at low or high concentrations (based on COHb), platelet function and measures of intravascular thrombus formation were decreased in mice and rats [18][19][20][21][22][23].…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Anmentioning
confidence: 91%
See 3 more Smart Citations
“…In other in vitro and in vivo investigations involving either mice or rats [24][25][26][27], COHb concentrations varied following CORM exposure, with little increase seen with CORMs that release CO quickly (e.g., CORM-3, tricarbonyldichloro(glycinato)ruthenium (II)), contrasted with COHb values between 8% to 17% after exposure to slow releasing CORMs (e.g., CORM-A1, sodium boranocarbonate, Na 2 [H 3 BCO 2 ]). In sum, when exposed to CO at low or high concentrations (based on COHb), platelet function and measures of intravascular thrombus formation were decreased in mice and rats [18][19][20][21][22][23].…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Anmentioning
confidence: 91%
“…While in vivo human investigation of the effect of CO is lacking, there are preclinical rodent models that demonstrate a profibrinolytic and/or antiplatelet effect in vitro and in vivo [18][19][20][21][22][23]. In hypercholesterolemic mice, upregulation with HO-1 with an adenovirus or exposure to inhaled CO (250 parts per million), decreased thrombus formation following carotid angioplasty, with a decrease in arterial tissue activity of plasminogen activator inhibitor-1, noted [18].…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, all these pathological phenotypes were rescued by administration of CO gas. In another study by Chen et al, 15 it was shown that in carotid arteries injury model of apolipoprotein E-deficient mice a significant antithrombotic effect can be achieved by exposition to CO inhalation (250 ppm) for 2 hours or by treatment with an adenovirus bearing the HO-1 gene.…”
mentioning
confidence: 99%